2019
DOI: 10.1007/s12274-019-2531-4
|View full text |Cite
|
Sign up to set email alerts
|

Real time imaging of two-dimensional iron oxide spherulite nanostructure formation

Abstract: The formation of complex hierarchical nanostructures has attracted a lot of attention from both the fundamental science and potential applications point of view. Spherulite structures with radial fibrillar branches have been found in various solids; however, their growth mechanisms remain poorly understood. Here, we report real time imaging of the formation of twodimensional (2D) iron oxide spherulite nanostructures in a liquid cell using transmission electron microscopy (TEM). By tracking the growth trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…To quantify the growth kinetics of MONT bundles under various reaction conditions, an image analysis routine was applied to individual frames of the collected LCTEM data, and change in average size with time is measured (Figure E, Figure S5, Figure S6). Growth rate ( G ) can be related to the activation energy (Δ E ) and temperature ( T ) as G = G 0 e –Δ E / kT where G 0 is a constant depending on the growth conditions and k is Boltzmann’s constant . Several factors such as precursor concentration and activation energy affect the size and growth rate of MONT bundles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the growth kinetics of MONT bundles under various reaction conditions, an image analysis routine was applied to individual frames of the collected LCTEM data, and change in average size with time is measured (Figure E, Figure S5, Figure S6). Growth rate ( G ) can be related to the activation energy (Δ E ) and temperature ( T ) as G = G 0 e –Δ E / kT where G 0 is a constant depending on the growth conditions and k is Boltzmann’s constant . Several factors such as precursor concentration and activation energy affect the size and growth rate of MONT bundles.…”
Section: Resultsmentioning
confidence: 99%
“…Growth rate (G) can be related to the activation energy (ΔE) and temperature (T) as G = G 0 e −ΔE/kT where G 0 is a constant depending on the growth conditions and k is Boltzmann's constant. 33 Several factors such as precursor concentration and activation energy affect the size and growth rate of MONT bundles. In addition, with LCTEM effects such as confinement, electron beam intensity, and liquid thickness, radiolysis reactions cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Zheng, Du, and co-workers investigated the formation of 2D spherulite iron oxide from the solution mixture of iron nitrate, oleylamine, oleic acid, and benzyl by LCTEM. 432 The in situ observations uncovered that the spherulite nanostructure showed a linear (at the early stage) and nonlinear (at the later stage) growth dynamics combined process, and a secondary nucleation was responsible for the formation of fibrillar branch structures. Moreover, for the crystallization of Fe 3 O 4 , the coexistence of the two pathways was confirmed: (1) ferrihydrite as the intermediates and (2) direct formation of magnetite, which are different from the amorphous iron oxide to magnetite pathway in an iron chloride solution reported by Faivre et al 428,432 The results indicate the possible multiple nucleation pathways for the crystallization of magnetite.…”
Section: Barium Sulfate (Basomentioning
confidence: 93%
“…The formation of spherulite Fe 3 O 4 from the mixture solution containging iron nitrate, oleylamine, oleic acid, and benzyl. 432 Direct nucleation + ferrihydrite to magnetite TEM…”
Section: Copper Oxides (Cuo and Cu 2 O)mentioning
confidence: 99%
“…Interestingly, the dendritic morphology evolution observed during the growth of iron oxide nanodendrites was remarkably consistent with existing theoretical predictions, despite occurring at the nanoscale. 50,51 Interests in metal dendrites stem from the fact that their growth is a primary cause for short-circuit failures in rechargeable batteries and other electronic devices. In a study of the crystallization and morphology evolution of lead dendrites, 16 we observed dendrite growth through tip splitting and dissolution of dendrites with mass loss when electric biasing was reversed (Figure 5c).…”
Section: Understanding Nanodendrite Pattern Formationmentioning
confidence: 99%